Nitrogen requirements for cabbage (brassica olerecea capitata) transplants and crop response to spacing and nitrogen top-dressing - Soundy, Puffy (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Horticulture))--University of Pretoria, 2005.